PUBLIC SAVINGS AT PT. BANK NTT (PERSERO) MAIN BRANCH KUPANG AND THE FACTORS AFFECTING THEM - Leki, Salomon; Perseveranda, M.E; Ketmoen, Adrianus; Indrawati, Agnes Susanti; Daok, Angelina Wulandari (Jurnal Ilmiah Ekonomi Bisnis, 2025)
The formulation of the problem in this study is (1) Whether the interest rate, inflation rate, and Regional Minimum Wage have a partial effect on the community's savings at PT. Bank NTT (Persero) Kupang Main Branch Unit?; (2) How do interest rates, inflation and regional minimum wages affect the level of public savings at PT. Bank NTT (Persero) Kupang Main Branch Unit? The purpose of this study is to analyze the influence of interest rates, inflation rates, and regional minimum wages on the amount of savings, both partially and simultaneously. The analysis technique used is quantitative analysis using a multiple linear regression model. In this study, the smallest square regression approach (Ordinary Least Square) was also used. The results of this analysis show that simultaneously: interest rates, inflation rates, and regional minimum wages have a significant effect on savings. Meanwhile, partially, interest rates have a significant positive effect on savings, while inflation and the regional minimum wage have a negative but significant effect. The value of the determination coefficient was 0.115 which indicates that 15.5% of the variation in savings can be explained by all three variables, while the remaining 84.5% is influenced by other factors outside the model. The researcher suggested that Bank NTT needs to strengthen the innovation of savings products and digital financial services in order to be able to increase public fund collection.